The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/0101-31572004-1636
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy independence and floating exchange rates: what does the Brazilian evidence tell us?

Abstract: ABSTRACT Some authors have advocated that shifting from fixed exchange rates to floating regimes has not delivered better economic outcomes to developing countries. As the argument goes, pervasive fear of floating in these economies has prevented drops in real interest rates and, more importantly, has been a hindrance in the way towards more monetary policy autonomy. This paper presents evidence suggesting this may not be the case for Brazil. More precisely, there are signs that fear of floating was le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…Similarly, the Brazilian inflation targeting regime employs the selic rate as the primary monetary policy instrument. Goncalves (1993) indicated that the shifting from fixed to floating exchange rates has not resulted in improved economic outcomes for developing countries. It is clear that the fear of floating was less acute due to low exchange rate pass-through and the policymakers focusing on monetary policy primarily.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Brazilian inflation targeting regime employs the selic rate as the primary monetary policy instrument. Goncalves (1993) indicated that the shifting from fixed to floating exchange rates has not resulted in improved economic outcomes for developing countries. It is clear that the fear of floating was less acute due to low exchange rate pass-through and the policymakers focusing on monetary policy primarily.…”
Section: Introductionmentioning
confidence: 99%
“…Outros autores também tratam da mudança do regime cambial em janeiro de 1999, dentre os quais destacam-se: Bevilaqua e Garcia (2002);Gonçalves (2004);Assis (2002); Frankel (2003) eGoldfajn (2002).…”
unclassified
“…Os resultados das séries simuladas apontam que choques monetários possuem efeito negativo e relevante no produto. Além disso, no período de baixa inflação, o grau de persistência da taxa de inflação diminuiu e os choques de política, identificados como choques na taxa de juros (1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), alta inflação (1985-1994) e período de câmbio fixo e flutuante em Soares (2004). O autor estima para os dois regimes uma regra de política e curva de Phillips.…”
Section: Resultados Naunclassified